Innovative progress in graphene derivative-based composite hybrid membranes for the removal of contaminants in wastewater: A review. (November 2022) - Kamran, Urooj; Rhee, Kyong Yop; Lee, Seul-Yi; Park, Soo-Jin
Abstract: Graphene derivatives (graphene oxide) are proved as an innovative carbon materials that are getting more attraction in membrane separation technology because of its unique properties and capability to attain layer-to-layer stacking, existence of high oxygen-based functional groups, and generation of nanochannels that successively enhance the selective pollutants removal performance. The review focused on the recent innovations in the development of graphene derivative-based composite hybrid membranes (GDHMs) for the removal of multiple contaminants from wastewater treatment. To design GDHMs, it was observed that at first GO layers undergo chemical treatments with either different polymers, plasma, or sulfonyl. After that, the chemically treated GO layers were decorated with various active functional materials (either with nanoparticles, magnetite, or nanorods, etc.). By preparing GDHMs, properties such as permeability, porosity, hydrophilicity, water flux, stability, feasibility, mechanical strength, regeneration ability, and antifouling tendency were excessively improved as compared to pristine GO membranes. Different types of novel GDHMs were able to remove toxic dyes (77–100%), heavy metals/ions (66–100%), phenols (40–100%), and pharmaceuticals (74–100%) from wastewater with high efficiency. Some of GDHMs were capable to show dual contaminant removal efficacy and antibacterial activity. In this study, it was observed that the most involved mechanisms for pollutants removal are size exclusion, transport, electrostatic interactions, adsorption, and donnan exclusion. In addition to this, interaction mechanism during membrane separation technology has also been elaborated by density functional theory. At last, in this review the discussion related to challenges, limitations, and future outlook for the applications of GDHMs has also been provided. Graphical abstract: Image 1 Highlights: Innovative progress in graphene derivatives-based hybrid membranes are highlighted. Graphene analogs-based hybrid membranes show high pollutants removal potential. Review of the last 5 years of graphene-based hybrid membranes is briefly addressed. Composites modifications improved the separation efficiency of hybrid membranes.